Occupational therapy for complex inpatients with stroke: identification of occupational needs in post-acute rehabilitation setting. Issue 9 (24th April 2018) - Schiavi, Margherita; Costi, Stefania; Pellegrini, Martina; Formisano, Debora; Borghi, Sergio; Fugazzaro, Stefania
Abstract: Purpose: Inpatients admitted to rehabilitation express needs not linked to disease causing hospitalization. This observational cross-sectional study identifies features and occupational needs of complex inpatients during rehabilitation, focusing on function and ability, regardless of diagnosis. Method: This study included sixteen adult inpatients with stroke, deemed complex according to Rehabilitation Complexity Scale-Extended, at admission to Rehabilitation ward (from July 2014 to February 2015). Patients with primary psychiatric disorders, language barriers, cognitive or severe communication deficits were excluded. Upon admission, a multidisciplinary team collected data on general health, independence in daily activities (Modified Barthel Index), fatigue (Fatigue Severity Scale), resistance to sitting and ability to perform instrumental activities (Instrumental Activities of Daily Living). The occupational therapist identified occupational needs according to Canadian Occupational Performance Measure. Results: Inpatients enrolled in this study were dependent in basic ADL, limited in instrumental ADL and easily fatigable. Their occupational needs related to self-care (75%) and, to a lesser extent, productivity (15%) and leisure (10%). According to inpatients, rehabilitation process should firstly address self-care needs, followed by productivity and leisure problems. Conclusions: Despite small sample size, this study described patterns of occupational needs in complex inpatients with stroke. These results will be implemented in client-centered rehabilitation programs to be tested in a phase-two trial. [NCT02173197] Implications for Rehabilitation: Priority occupational needs of complex inpatients with stroke during rehabilitation are focused on self-care area. Productivity and leisure problems also arise in early post-acute phase. Client-centered rehabilitation programs should firstly address self-care needs and, later on, they should also focus on the recovery of family and social roles.